Effects of interventions for self-harm in children and adolescents : a systematic review and meta-analysis - Johansson, Björn Axel; Wilbe Ramsay, Karin; Pettersson, Agneta; Bjureberg, Johan (European Child and Adolescent Psychiatry, 2025)
Self-harm, including nonsuicidal self-injury and suicide attempts, is common among youth, associated with elevated psychopathology, suicide risk, and increased demand for clinical services. Despite advances in understanding and treatment, few interventions have demonstrated efficacy in randomized controlled trials (RCTs), which are considered the gold standard for evaluating treatment effects by randomly assigning participants to intervention or control groups. Building on prior meta-analyses, this study conducted a meta-analysis of RCTs to evaluate the efficacy of interventions in adolescents across three outcomes: self-harm regardless of suicidal intent, suicide attempts, and nonsuicidal self-injury. Systematic searches in PsycINFO, Cochrane Library, Embase, and Medline identified RCTs evaluating interventions for self-harm in youth under 18 years who engaged in self-harm at least once in the past six months. Studies were included if 80% met these criteria. Meta-analyses were conducted using random-effects modeling, primarily to account for heterogeneity across studies, as this approach accommodates variation in effect sizes that may arise from differences in for example study populations, and interventions. Certainty of evidence was assessed using GRADE. Of 6497 screened records, 21 studies met inclusion criteria. Meta-analysis showed that across three studies, Dialectical Behavior Therapy (DBT) reduced the number of adolescents engaging in self-harm behaviors (risk difference [RD]=–0.12, 95% confidence interval: − 0.22 to − 0.02), with moderate certainty. Meta-analysis of two studies found Internet-delivered Emotion Regulation Individual Therapy for Adolescents (IERITA) reduced both the episodes (mean difference =–4.65, − 8.04 to − 1.25) and occurrence of nonsuicidal self-injury at treatment end (RD=–0.20, − 0.34 to − 0.07), with low certainty of evidence. DBT-A appears effective in preventing repeated self-harm, supported by findings across multiple research groups. The less resource-intensive therapy IERITA may be beneficial for adolescents with nonsuicidal self-injury. Larger sample sizes and consensus on definitions and measurement approaches will benefit future research and clinical practice. Prospero registration: ID CRD42023480178.
Keywords: Adolescents; Meta-analysis; Nonsuicidal self-injury; Self-harm; Suicide attempt; Treatment effects